Efficacy of N -methyl- D -aspartate receptor modulator augmentation in schizophrenia: A meta-analysis of randomised, placebo-controlled trials - Goh, Kah Kheng; Wu, Tzu-Hua; Chen, Chun-Hsin; Lu, Mong-Liang (Journal of psychopharmacology (Oxford), 2021)
Dysfunction of the -methyl- -aspartate glutamate receptor is involved in the putative pathology of schizophrenia. There is growing interest in the potential of -methyl- -aspartate receptor modulators to improve the symptoms of schizophrenia, but the evidence for the use of glutamatergic agents for augmenting schizophrenia remains inconclusive. We conducted a meta-analysis to test the efficacy and safety of -methyl- -aspartate receptor modulator supplements in patients with schizophrenia. Following a systemic search in MEDLINE, Embase, Cochrane and Scopus, 40 double-blinded, randomised, placebo-controlled trials involving 4937 patients with schizophrenia were included in this meta-analysis. The change in the severity of symptoms among patients with schizophrenia was defined as the primary outcome, whereas the safety profiles of the intervention, including the discontinuation rate and adverse events, were defined as secondary outcomes. When added to antipsychotic treatments, -methyl- -aspartate receptor modulators improved multiple schizophrenia symptoms, particularly negative symptoms, and had satisfactory side effects and safety profile. Among the seven glutamatergic agents analysed, glycine, D-serine and sarcosine had better treatment profiles than other agents, and NMDA receptor co-agonists, as a group, provided a reduction in schizophrenia symptoms compared to antipsychotic treatments without supplementation. Augmentation with -methyl- -aspartate receptor modulators was only effective among patients treated with antipsychotics other than clozapine. The results indicate that -methyl- -aspartate receptor modulators, particularly with glycine, D-serine and sarcosine, are more beneficial than the placebo in treating schizophrenia, and the effects extended to both positive and negative symptoms, when augmented with antipsychotics other than clozapine.